2010
DOI: 10.1021/ma1000173
|View full text |Cite
|
Sign up to set email alerts
|

Fracture and Self-Healing in a Well-Defined Self-Assembled Polymer Network

Abstract: We studied shear-induced fracture and self-healing of well-defined transient polymer networks formed by telechelic polypeptides, with nodes formed by collagen-like triple helices. When these gels are sheared at a rate that is higher than the inverse relaxation time of the nodes, fracture occurs at a critical stress which increases logarithmically with increasing shear rate. When a constant stress is applied, fracture occurs after a delay time that decreases exponentially with increasing stress. These observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
159
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(173 citation statements)
references
References 24 publications
13
159
1
Order By: Relevance
“…3C) likely through restoration of broken catecholato-Fe 3þ cross-links analogous to what has been observed in other types of reversible polymer networks with weaker noncovalent crosslinks such as ionic and hydrogen bonds (22,23). The effects of polymer size, cross-link density, and Fe∶dopa ratio on the relaxation and self-healing time of catecholato-Fe 3þ cross-linked polymer networks are currently under investigation.…”
Section: Discussionmentioning
confidence: 68%
“…3C) likely through restoration of broken catecholato-Fe 3þ cross-links analogous to what has been observed in other types of reversible polymer networks with weaker noncovalent crosslinks such as ionic and hydrogen bonds (22,23). The effects of polymer size, cross-link density, and Fe∶dopa ratio on the relaxation and self-healing time of catecholato-Fe 3þ cross-linked polymer networks are currently under investigation.…”
Section: Discussionmentioning
confidence: 68%
“…18 This was interpreted as evidence of a 'fluidization' zone in the vicinity of a microscopic fracture plane that grew in thickness with increasing shear rate, possibly corresponding to localized fracture of the gel into smaller fragments.…”
Section: Theoretical Analysis and Discussionmentioning
confidence: 99%
“…Berret et al 7,9 in the shear-thinning regime of aqueous telechelic polymer solutions and by Skrzeszewska et al 26 for telechelic polypeptides; in these studies, the stress maxima were demonstrated by particle image velocimetry, a flow visualization technique, to be due to the formation of a fracture zone within the sample. 9,26 In our solutions, deformation energies of 3-4…”
Section: Rate-dependent Mechanical Instabilitymentioning
confidence: 99%